Reversing and modulating cellular senescence in beta cells, a new field of opportunities to treat diabetes - Rubin de Celis, Maria F.; Bonner-Weir, Susan (Frontiers in Endocrinology, 2023)
Diabetes constitutes a world-wide pandemic that requires searching for new treatments to halt its progression. Cellular senescence of pancreatic beta cells has been described as a major contributor to development and worsening of diabetes. The concept of reversibility of cellular senescence is critical as is the timing to take actions against this "dormant" senescent state. The reversal of cellular senescence can be considered as rejuvenation of the specific cell if it returns to the original "healthy state" and doesn't behave aberrantly as seen in some cancer cells. In rodents, treatment with senolytics and senomorphics blunted or prevented disease progression, however their use carries drawbacks. Modulators of cellular senescence is a new area of research that seeks to reverse the senescence. More research in each of these modalities should lead to new treatments to stop diabetes development and progression Gut Microbiota, an Additional Hallmark of Human Aging and Neurodegeneration.